Covid 19 Prevention Education to Pregnant Mothers In The Sub-District of Medan Sunggal, Medan City in 2o22 - Willhelmina Wahara (IJCS: International Journal of Community Service, 2022)
Coronavirus is a large family of viruses that cause diseases ranging from mild to severe symptoms and can even cause death. Pregnant women are one of the groups vulnerable to being exposed to the coronavirus which will endanger the health of the mother and the fetus she is carrying. One way to prevent transmission to pregnant women is to wash your hands frequently with soap or a hand-sanitizer for 20 seconds, wear a mask when leaving the house and practice the correct etiquette of coughing and sneezing. The area around Sunggal Village is a coronavirus red zone in Medan City. the purpose of this service is to increase knowledge about how to prevent coronavirus in pregnant women in Sunggal village, Medan City. The method used in this service is to provide health education through a leaflet that is distributed directly to the target audience of 40 pregnant women affected by the coronavirus. The results of the evaluation show that there is an increase in the knowledge of the target audience about how to wash hands and use masks correctly from less knowledge (21%), moderate (65%), good (24%) to moderate knowledge (15%) and good (85%). This activity will improve hygiene and healthy living habits that can help prevent Coronavirus transmission to pregnant women so that it will reduce morbidity and mortality rates for mothers and fetuses.